Electron Microscopy of Interfaces in Au/Cu Multilayer on Si, Li(Ni,Mn)xOy on Nb-doped SrTiO3 and Nanocomposite Steel - Singh, Ankit (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Electron Microscopy; Au/Cu Multilayer; on Si, Li(Ni,Mn)xOy; Nb-doped SrTiO3; Nanocomposite Steel